PROSES KOGNITIF SISWA DALAM PEMECAHAN MASALAH MATEMATIKA - Binur Panjaitan (Universitas Negeri Malang, 2013)
Abstract: Students' Cognitive Processes in Solving Mathematics Problems. The purpose of this qualitative study is to obtain descriptions of students' cognitive processes in solving mathematical problems based on cognitive style and gender. The selection of the subjects in this qualitative research was based on field independent and field dependent cognitive styles. Four subjects, two boys and two girls, were involved in the study; a girl and a boy were of field independent cognitive style and the other couple were of field dependent one. The four subjects were students of the eighth grade of State Junior High School of Siborongborong, North Tapanuli district, North Sumatera. The results  of this reserach indicate that the profile of the cognitive processes of the four subjects are different. Abstrak: Proses Kognitif Siswa dalam Pemecahan Masalah Matematika. Tujuan penelitian ini adalah untuk memeroleh deskripsi proses kognitif siswa dalam pemecahan masalah matematika berdasarkan gaya kognitif dan gender. Penelitian ini merupakan penelitian kualitatif. Pemilihan subjek berdasarkan gaya kognitif field independent dan field dependent. Subjek yang memiliki gaya kognitif field independent terdiri atas satu anak laki-laki dan satu anak perempuan, subjek yang memiliki gaya kognitif field dependent terdiri atas satu anak laki-laki dan satu anak perempuan. Keempat subjek tersebut adalah siswa kelas delapan SMP Negeri Siborongborong Kabupaten Tapanuli Utara Provinsi Sumatera Utara. Hasil penelitian menunjukkan bahwa profil proses kognitif keempat subjek berbeda.